Anna - Wadhams, Margaret (The Bodley Head Ltd, 1986)
Anna, who has eczema, and her friend Mandy, who has psoriasis, both struggle to be accepted by other children who do not understand the nature of these skin conditions.
Keywords: Juvenile literature-Fiction